ERUPTIVE XANTHOMA IN A YOUNG ADULT MALE WITH SEVERE DYSLIPIDEMIA AND NEWLY DIAGNOSED TYPE 1 DIABETES - Capulong Linsao, Ma. Jean; Gutierrez-Benavidez, Mary Jane (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Eruptive xanthomas are multiple, red-yellow papules that appear in crops on the extensor surface of the extremities and the buttocks and are pathognomonic skin manifestations of severe hypertriglyceridemia, especially in patients with newly diagnosed or decompensated diabetes mellitus. In the Philippines, there are no nationwide prevalence or incidence studies on Type 1 Diabetes, particularly those in association with dyslipidemia and eruptive xanthoma formation. CASE This report provides a comprehensive view of the unusual case of an adult male, who was managed as a case Eruptive Xanthoma secondary to Dyslipidemia and Type 1 Diabetes. CONCLUSION This case recognizes the importance of prompt awareness and recognition of eruptive xanthoma and its association with dyslipidemia, and newly diagnosed or decompensated diabetes mellitus to help prevent its serious complications with timely evaluation and therapy, and consequently decrease morbidity and mortality.